Resources
Testimonials
Plans
Sign in
Sign up
Resources
Testimonials
Plans
AI tutor
Welcome to Bytelearn!
Let’s check out your problem:
Evaluate the expression for
y
=
1
y = 1
y
=
1
.
\newline
Write your answer in simplest form.
\newline
y
−
9
−
y
+
5
=
\frac{y - 9}{-y + 5} =
−
y
+
5
y
−
9
=
__
View step-by-step help
Home
Math Problems
Algebra 2
Evaluate rational expressions II
Full solution
Q.
Evaluate the expression for
y
=
1
y = 1
y
=
1
.
\newline
Write your answer in simplest form.
\newline
y
−
9
−
y
+
5
=
\frac{y - 9}{-y + 5} =
−
y
+
5
y
−
9
=
__
Identify Expression:
Identify the expression after substituting
y
=
1
y = 1
y
=
1
\newline
Substitute
1
1
1
for
y
y
y
in
y
−
9
−
y
+
5
\frac{y - 9}{-y + 5}
−
y
+
5
y
−
9
.
\newline
1
−
9
−
1
+
5
\frac{1 - 9}{-1 + 5}
−
1
+
5
1
−
9
Substitute and Simplify:
Evaluate
1
−
9
1 - 9
1
−
9
\newline
1
−
9
=
−
8
1 - 9 = -8
1
−
9
=
−
8
\newline
Numerator:
−
8
-8
−
8
Evaluate Numerator:
Evaluate
−
1
+
5
-1 + 5
−
1
+
5
\newline
−
1
+
5
=
4
-1 + 5 = 4
−
1
+
5
=
4
\newline
Denominator:
4
4
4
Evaluate Denominator:
−
8
4
-\frac{8}{4}
−
4
8
\newline
Rewrite the
fraction
in simplest form.
\newline
Divide both
−
8
-8
−
8
and
4
4
4
by
4
4
4
to simplify.
\newline
−
8
4
=
−
2
-\frac{8}{4} = -2
−
4
8
=
−
2
More problems from Evaluate rational expressions II
Question
Evaluate the expression for
t
=
−
4.4
t = -4.4
t
=
−
4.4
.
\newline
Write your answer in simplest form.
\newline
` frac{t - 4}{t - 2} =` ____
Get tutor help
Posted 1 year ago
Question
Simplify. Write your answer using whole numbers and variables.
\newline
g
3
g
2
−
4
g
\frac{g}{3g^2 - 4g}
3
g
2
−
4
g
g
Get tutor help
Posted 9 months ago
Question
Simplify. Express your answer as a single fraction in simplest form.
3
2
−
5
p
3
3
\frac{3}{2} - \frac{5p^3}{3}
2
3
−
3
5
p
3
______
Get tutor help
Posted 9 months ago
Question
Simplify. Express your answer as a single fraction in simplest form.
\newline
1
+
v
5
w
3
1 + \frac{v^5w}{3}
1
+
3
v
5
w
\newline
______
Get tutor help
Posted 9 months ago
Question
Solve for
h
h
h
.
\newline
−
5
h
−
2
=
−
4
h
−
3
\frac{-5}{h - 2} = \frac{-4}{h - 3}
h
−
2
−
5
=
h
−
3
−
4
\newline
There may be
1
1
1
or
2
2
2
solutions.
\newline
h
=
h =
h
=
_____ or
h
=
h =
h
=
_____
Get tutor help
Posted 1 year ago
Question
What is the equation of the vertical asymptote of
y
=
1
x
+
9
y = \frac{1}{x + 9}
y
=
x
+
9
1
? _____
Get tutor help
Posted 1 year ago
Question
What is the excluded value for
y
=
1
x
−
9
−
9
y = \frac{1}{x - 9} - 9
y
=
x
−
9
1
−
9
?
\newline
______
Get tutor help
Posted 1 year ago
Question
Simplify. Write your answer using whole numbers and variables.
\newline
9
k
+
4
9
k
2
+
4
k
\frac{9k + 4}{9k^2 + 4k}
9
k
2
+
4
k
9
k
+
4
\newline
______
Get tutor help
Posted 1 year ago
Question
Divide. Write your answer in simplest form.
\newline
g
−
1
10
g
3
+
25
g
2
÷
(
g
−
1
)
\frac{g- 1}{10g^3 + 25g^2} \div (g- 1)
10
g
3
+
25
g
2
g
−
1
÷
(
g
−
1
)
\newline
______
Get tutor help
Posted 1 year ago
Question
Simplify. Express your answer as a single fraction in simplest form.
\newline
5
−
3
t
3
1
\frac{5 - \frac{3}{t^3}}{1}
1
5
−
t
3
3
\newline
______
Get tutor help
Posted 1 year ago
Related topics
Algebra - Order of Operations
Algebra - Distributive Property
`X` and `Y` Axes
Geometry - Scalene Triangle
Common Multiple
Geometry - Quadrant